Audit Committee Diversity and Firm Performance in Malaysia - Shamsol, Nurul Farisha; Amir, Aliana Shazma (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2025)
This study examines the relationship between audit committee diversity and financial performance. The research analyzes data from the top 100 non-financial firms listed on Bursa Malaysia in 2021. While extensive literature explores the connection between audit committees and financial firm performance, limited studies investigate their role in overall firm performance. Thus, this study aims to bridge this gap by examining key audit committee attributes—independence, meeting frequency, and expertise—and their impact on firm performance. Grounded in Agency Theory, this study posits that an independent and well-structured audit committee enhances monitoring effectiveness, mitigating agency conflicts, and improving firm performance. The empirical findings reveal a positive and significant relationship between audit committee independence, audit committee meetings, and audit committee expertise with firm performance, measured by return on assets. Additionally, firm size exhibits a significant positive association with firm performance. The study contributes to the growing body of corporate governance literature by providing empirical evidence on the role of audit committee attributes in firm performance. The findings underscore the importance of audit committee effectiveness in enhancing corporate governance and business outcomes. The paper concludes with a discussion on implications, limitations, and recommendations for future research